Ketidakpatuhan Australia Terhadap Antarctic Treaty dengan Penempatan Militer di Antartika - Fakhriza Naufal Rakin; Satwika Paramasatya (Journal of International Relations Diponegoro, 2022)
This study aims to explain Australia's non-compliance with the Antarctic Treaty regime that they had previously ratified by placing military technology on the "peaceful" continent of Antarctica, which is the choice made by the Australian government at this time. Australia is one of the important figures in the Antarctic Treaty regime where Australia is a country that has the largest claim area in Antarctica and is a country that strongly promotes the Antarctic Treaty with the desire that Antarctica can become a continent that will only be used for peaceful purposes and research to advance science. But recently Australia took the decision to violate the rules of the regime that they had agreed to and ratified by disobeying the regime where Australia carried out military deployments and military technology in Antarctica which Australia did openly and knowingly that its actions had breaking the rules of the regime. The data collected in this study used the documentation method. This research will use the method of Compliance Theory and Rational Choice Theory. This research will try to explain Australia's non-compliance with the international regime it has ratified and promoted and the factors that drive its non-compliance.